Anodisation of Aluminium Alloys by Micro-Capillary Technique as a Tool for Reliable, Cost-Efficient, and Quick Process Parameter Determination. (8th March 2016) - Nickel, Daniela; Dietrich, Dagmar; Morgenstern, Roy; Scharf, Ingolf; Podlesak, Harry; Lampke, Thomas
Abstract : Anodisation is essential for improving surface properties of aluminium alloys and composites regarding wear and corrosion behaviour. Optimisation of the anodising process depends on microstructural constituents contained in aluminium alloys and represents a key task, consisting of the control of process parameters and electrolyte formulation. We applied the micro-capillary technique known from corrosion studies and modified it to form anodic aluminium oxide films on high-strength aluminium alloys in comparison to pure aluminium in sulphuric acid. A glass capillary with an opening of 800 μ m in diameter was utilized. Corresponding electrochemical measurements during potentiodynamic and potentiostatic anodisation revealed anodic current responses similar to conventional anodisation. The measurement of film thickness was adapted to the thin anodised spots using ellipsometry and energy dispersive X-ray analysis. Cross sections prepared by focused ion beam milling confirm the thickness results and show the behaviour of intermetallic phases depending on the anodising potential. Consequently, micro-capillary anodising proved to be an effective tool for developing appropriate anodisation conditions for aluminium alloys and composites because it allows quick variation of electrolyte composition by applying low electrolyte volumes and rapid film formation due to short process durations at small areas and more flexible variation of process parameters due to the used set-up.